3D game development for cobot-human interaction using unity - Wang, Zihang (Nanyang Technological University, 2022)
Cobot is a powerful robot in the factory. At present, more and more industries are inseparable from cobot. The project aims to develop a VR game for Cobot-Human interaction by using Unity. The VR headset and controllers will record down the user’s real-time movement data. Then these data will be sent to Cobot and affect the behaviour of the Cobot. In the game, player will work with Cobot in a Packing Factory to package the food base on customer’s order. The food and package will be conveyed by conveyor belt. Player needs to package the correct food and deliver package. Player can select the difficulty in the game. Different difficulty shows the power of cobot. The game will help people to know cobot and that will also be easy to help people to investigate a new generation of cobot.